Negotiating knowledge: The role of network hedging in the production of high-impact science - Adrián A. Díaz-Faes; Pablo D’Este; Anne L. J. Ter Wal (PLoS ONE, 2026)
Extant research shows that knowledge networks with a greater diversity of participants and richer in structural holes are more conducive to advancing science and innovation. However, research on network structure and network composition tends to overlook how actors might best utilize their connections. In this study, we seek to unpack the variation in how individuals leverage the opportunities afforded by their networks, focusing on the scientific knowledge production process. Given the uncertainty faced by scientists during the different stages of the research process, we argue that network hedging – consulting multiple individuals for the same resource need – rather than network compartmentalization – turning to a particular network contact for a specific resource need – increases the likelihood of research findings with greater scientific impact. By analyzing granular data on the network mobilization decisions and scientific outputs for a sample of biomedical scientists, we find support for our prediction that network hedging is positively associated with the production of high-impact scientific output, and that this effect is manifest beyond the benefits of being embedded in more diverse or sparser networks.